Cluster Development in Poland a Diagnostic Study - Romaniuk, Krystyna (Olsztyn Economic Journal, 2012)
The objective of this study was to evaluate cluster development in Poland based on the results of research conducted over the last decade as well as current information published by the Polish Agency for Enterprise Development and the "Portal Innowacji" web portal. Research results show that Polish clusters are relatively new structures, and the majority of them are still at the embryonic stage of development. The structure of some Polish clusters differs from that described in the classical cluster theory, while the attributes of other are typical. In Poland, cluster development is financed mostly from the European Structural Funds. Thus, changes in EU policy and focus on international cluster initiatives may considerably slow down the process